A rare case of Gynura-segetum-related hepatic sinus obstruction syndrome complicated with alcoholic liver disease - Yidan Gao; Xiangbo Zhang; Xiang Zhou; Jie Wang; Ling Gong; Gongying Chen (Journal of the Pakistan Medical Association, 2024)
Hepatic sinus obstruction syndrome (HSOS) is easy to be misdiagnosed or missed, and there is no unified and effective treatment for it. A patient was considered to have Budd-Chiari syndrome. He underwent a transjugular liver biopsy, and pathological examination revealed HSOS without liver cirrhosis. After the failure of anticoagulation therapy, he successfully received a transjugular intrahepatic portosystemic shunt (TIPS). After discharge, he was followed-up for four years with a good prognosis. G. segetum-induced HSOS can be easily overlooked, especially in patients with underlying liver diseases. When medical therapy fails, TIPS can control ascites and portal hypertension, and the long-term prognosis is optimistic. Key words: Gynura segetum; Hepatic sinusoidal obstruction syndrome; Transjugular intrahepatic portosystemic shunt.